LAND USE AND RECREATION VALUES IN RURAL GERMANY: A HEDONIC PRICING APPROACH - Wüstemann, Henry (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
Rural landscapes provide a high variety of environmental and recreational benefits, yet knowledge of the amenity values associated with land use is still limited. This paper analyses the amenity values associated with different land uses by applying the Hedonic Pricing Method (HPM). The sample consists of 986 rental prices for holiday apartments and cottages in Germany for 2013. The data set provides detailed information on several structural variables such as size and capacity of the accommodation. In order to analyse the impact of land use on rental prices, we incorporated coverage variables for the six land use and ecosystem types: forest, arable land, grassland, freshwater (rivers and lakes), marine water and wetlands. We further investigated the impact of the distance to the nearest major city on rental prices to control for additional location variables. The results show a capitalisation of structural and land use variables in rental prices. Among the land use variables, the coverage of rivers and lakes, marine waters and wetlands in a 20 km-buffer around the accommodation in particular has a high positive impact on the price variable. Additionally, the results show an inverse relation between rental prices and high shares of pastures, arable and forestland, suggesting tourists’ preferences towards more diverse landscapes.